DEVELOPMENT OF THE ARABIC-INDONESIAN DICTIONARY AND INDONESIAN-ARABIC DICTIONARY (HISTORICAL AND SYSTEMATIC STUDY IN INDONESIA) - mohd fikri azhari (STAI Hubbulwathan Duri, 2020)
This study aims to identify and describe: 1) the development of Arab-Indonesian and Indonesian-Arab literacy in Indonesia, 2) the Arab-Indonesian and Indonesian-Arab literacy system in Indonesia. This study is a historical study, with a qualitative approach. The data collection in this study uses the technique of documentation. The data analysis used in this study used qualitative descriptive analysis, with the focus of the study being the development of Arab-Indonesian and Indonesian-Arab studies in Indonesia. The results of this study indicated that the development of lexicography Arabic-Indonesian and Indonesian-Arabic in Indonesia can be summed up as follows: First, a) The initial phase of lexicography Arabic-Indonesian begins with the rise of Arab-Malay dictionary Idris Al-Marbawi in 1927. The dictionary is the beginning of the development of the Indonesian-Indonesian dictionary in Indonesia. Once the presence of Arab-Malay dictionary Idris Al-Marbawi then comes the Arabic-Indonesian dictionary compiled by Mahmud Yunus in 1972. The initial phase-Indonesian Arabic lexicography is followed by a phase of development of lexicography Arabic-Indonesian dictionary Al-Munawwir in 1984, then Dictionary Contemporary Arabic-Indonesian 1996, Al-Bisri Arabic-Indonesian Dictionary 1999, Al-Mutahar Arabic-Indonesian Dictionary, Al-Azhar Arabic-Indonesian Dictionary 2009, Al-Kamal Arabic-Indonesian Dictionary 2010. (b) Early phases of Indonesian-Arab practice in The introduction of the Indonesian-Arabic Dictionary was compiled by Asad M. Kalali in 1981. It is the forerunner of the Indonesian-Arabic dictionary in Indonesia. The early phases of the Arabic-Indonesian dictionary continue with the developmental phase of the Indonesian-Arabic dictionary of the Indonesian-Arabic Al-Bisri dictionary in 1999, the Indonesian-Arabic dictionary Al-Munawwir in 2007, the Indonesian-Arabic dictionary of Al-Mufied in 2010, the Indonesian- Arabic KABA 2013. Second, the Arabic-Indonesian and Indonesian-Arabic system of learning is still dominated by a special alphabetical system, where users (users) of these dictionaries need to know the basic grammar of a word, of course this system is very difficult to use for them who is not yet familiar with sharf and narcissism. But in the development phase there is also an Arabic-Indonesian dictionary using the articulation system, where the user (user) does not have to change or find the word pattern they want to look for, but instead refers to the first letter of a word. Of course, this system makes it easy for non-Arabs to find a dictionary.